Front Cover: Imidazolinium‐based Multiblock Amphiphile as Transmembrane Anion Transporter (2/2021). Issue 2 (30th December 2020) - Mori, Miki; Sato, Kohei; Ekimoto, Toru; Okumura, Shinichi; Ikeguchi, Mitsunori; Tabata, Kazuhito V.; Noji, Hiroyuki; Kinbara, Kazushi
Abstract : Ion transport across the cellular membranes is an important biological process in maintaining life. Here, the transmembrane ion transport properties of a newly developed imidazolinium‐based multiblock amphiphile (IMA ) are reported. IMA transports anions with selectivity for nitrate, recognizing anions via (C−H) + ⋅⋅⋅X − hydrogen bond with the C2 proton of the imidazolinium ring. The anion transport is achieved by a mobile carrier mechanism, where formation of dimeric complexes of IMA with anions in the lipid bilayer membranes was suggested by spectroscopic analysis and molecular dynamics simulation. More information can be found in the Full Paper by Kazushi Kinbara et al.